Pengembangan Sistem Terintegrasi Klinik dan Aplikasi Manajemen Obat Menggunakan Application Programming Interface (API) - Elvi Ningsih Telaumbanua; Fasrian Mauren Niella Hura; Juang Anjes Putra Telaumbanua; Carolina Sayangi Cahaya Waruwu; Syukur Famta Febriman Hura (Jurnal Informatika Terpadu, 2026)
The purpose of this study is to create a clinical information system that can be integrated with an Application Programming Interface (API) for drug management. Unintegrated management of patient and drug data is a major problem facing clinics. This can lead to duplicate data and recording errors. Needs analysis, system design, implementation, and testing are the stages of development for a software engineering approach. Observations, interviews, and literature studies were used to collect data. APIs and NIKs connect applications to the system. The results of the study show that the developed system can automatically and consistently integrate patient data and drug prescriptions into clinical applications and drug management. The results of the system test using the Black-Box Testing method show that all the system's main functions run as expected under the predetermined scenario, with a 100% test success rate. Based on these findings, this integrated system is recommended for small- to medium-scale clinics to improve service efficiency and data management accuracy. Overall, the study shows that APIs help integrate clinical information systems and medication management.